Phase-contrast imaging with synchrotron hard X-ray reveals the effect of icariin on bone tissue morphology and microstructure in rabbits with early glucocorticoid-induced osteonecrosis of the femoral head - Yang, Xu; Shi, Lijun; Li, Aifeng; Gao, Fuqiang; Sun, Wei; Li, Zirong (Frontiers in Cell and Developmental Biology, 2023)
Background: Phase-contrast imaging (PCI) with synchrotron hard X-ray was used to observe the changes in bone tissue morphology and microstructure in rabbit models of early glucocorticoid-induced osteonecrosis of the femoral head (ONFH), and to evaluate the intervention effect of Icariin. Methods: Fifty mature New Zealand rabbits (weighing 2.5-3.0 kg) were randomly divided into a control group (n=10), a glucocorticoid group (n=20), and an Icariin group (n=20). The glucocorticoid group and the Icariin group were sequentially injected with lipopolysaccharide (LPS) and methylprednisolone (MPS) to establish a glucocorticoid-induced ONFH animal model. The Icariin group was given Icariin solution when methylprednisolone was injected for the first time, and the control group and glucocorticoid group were given the same amount of normal saline. Animals were sacrificed after 6 weeks, and bilateral femoral head specimens were taken for research. The right femoral head was observed by PCI with synchrotron hard X-ray technology, and the left femoral head was verified by Micro-CT scanning and HE staining. Results: Forty-three animals (nine in the control group, sixteen in the glucocorticoid group, and eighteen in the Icariin group) were included in the study. PCI with synchrotron hard X-ray revealed that the trabecular bone in the glucocorticoid group was thinned, broken, and structurally damaged, whereas the trabecular bone in the Icariin group had normal volume, thickness, and a relatively intact structure. Micro-CT scan reconstruction and HE staining were used to verify the reliability of this technique in identifying osteonecrosis. Conclusion: The effects of Icariin were observed in an early glucocorticoid-induced ONFH rabbit model using PCI with synchrotron hard X-ray. Icariin weakens the destructive effect of glucocorticoids on bone tissue structure, improves bone tissue morphology, and stabilizes bone microstructure. This technique may provide a definitive, non-invasive alternative to histological examination for the diagnosis of early ONFH.